Chemical constituents and biological activity of Artocarpus altilis (Moraceae) and Micromelum minutum (Rutaceae) - Mohamed Shamaun, Shireen Shaharina (2008)
The species of Artocarpus altitis from the Moraceae family and Micromelum minutum from the Rutaceae family were phytochemically studied and screened for their biological activities. The first species, Artocarpus altitis (Parkinson) Fosberg was collected from Kelantan and Pahang. Micromelum Minutum (G. Forst.) Wight & Am. was collected from Sepilok, Sabah. The crude extracts and isolated compounds were screened for antimicrobial, cytotoxic and antioxidant activities using disc diffusion method, 1, 2-Diphenyl-2-picrylhydrazyl (DPPH) and Microculture Tetrazolium Salt (MTT) assays respectively. The microbes used for antimicrobial tests were methicilin resistant Staphylococcus aureus (MRSA), Bacillus subtilis and Pseudomonas aeruginosa.Detail study on the bark of Artocarpus altilis afforded cycloartocarpin (51), artocarpin (52), morusin (53), cycloartobiloxanthone (54) and artoindonesianin V (55). Chemical investigation on the root of Artocarpus altilis have resulted in the isolation of two new flavonoids, hydroxyartocarpin (56) and artocarpinin (57). Urs-12-en-3β-ol (58) and 6- methyl-β-D-glucopyranose (60) were isolated from the leaves of Micromelum minutum along with a coumarin known as 8-hydroxyisocapnolactone-2', 3'-diol (59). The leaves crude extract of Micromelum minutum gave strong cytotoxic activity towards HL 60 cell line and exhibited free radical scavenging activity towards DPPH. However, no activity was observed in the crude extract of Artocarpus altilis.